Calcium regulation of tension redevelopment kinetics with 2-deoxy-ATP or low [ATP] in rabbit skeletal muscle. - Regnier, M (1998)
The correlation of acto-myosin ATPase rate with tension redevelopment kinetics (k(tr)) was determined during Ca(+2)-activated contractions of demembranated rabbit psoas muscle fibers; the ATPase rate was either increased or decreased relative to control by substitution of ATP (5.0 mM) with 2-deoxy-ATP (dATP) (5.0 mM) or by lowering [ATP] to 0.5 mM, respectively. The activation dependence of k(tr) and unloaded shortening velocity (Vu) was measured with each substrate. With 5.0 mM ATP, Vu depended linearly on tension (P), whereas k(tr) exhibited a nonlinear dependence on P, being relatively independent of P at submaximum levels and rising steeply at P > 0.6-0.7 of maximum tension (Po). With dATP, Vu was 25% greater than control at Po and was elevated at all P > 0.15Po, whereas Po was unchanged. Furthermore, the Ca(+2) sensitivity of both k(tr) and P increased, such that the dependence of k(tr) on P was not significantly different from control, despite an elevation of Vu and maximal k(tr). In contrast, lowering [ATP] caused a slight (8%) elevation of Po, no change in the Ca(+2) sensitivity of P, and a decrease in Vu at all P. Moreover, k(tr) was decreased relative to control at P > 0.75Po, but was elevated at P < 0.75Po. These data demonstrate that the cross-bridge cycling rate dominates k(tr) at maximum but not submaximum levels of Ca(2+) activation.